The Effect of Fraud Triangle on Manufacture Financial Statement of Listed Companies in Indonesia Stock Exchange - Yesy Arafah (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Recently, we had seen many cases of fraud. Therefore, this research is aimed at the effect of financial stability, external pressure, personal financial need, financial targets and ineffective monitoring on the financial statement fraud. In this case, the independent variables involves financial stability, external pressure, personal financial need, financial targets, and ineffective monitoring. Meanwhile, the dependent variable is the financial statement fraud itself. In addition, the research population covers the listed companies in Indonesia Stock Exchange as of December 2020 and the samples are taken by using the purposive sampling method. Furthermore, the research also employs the financial statement taken from the Indonesia Stock Exchange site as secondary data. Moreover, Multiple Linear Regression Analysis is also performed in this research. As a conclusion, the variables of financial stability, external pressure, personal financial need, financial targets, and ineffective monitoring has resulted in the financial statement fraud